(untitled) (Academia Science Repository, 2023)
The work of Anna Akhmatova occupies one of the important places in the history of Russian literature of the twentieth century. It marked the terrible period of Yezhovshchina, which led Akhmatova to write the poem Requiem. This article discusses the artistic originality of the genre "Requiem" by Anna Akhmatova, the state of mind of the lyrical hero, the influence of the poem on readers, the statements of Alexei Pavlovsky, the culmination, as well as the analysis of the work by chapters and parts.